Magnetic induction heating and drug release properties of magnetic carbon nanotubes - Xudong Zuo; Dongmei Zhang; Jiandong Zhang; Tao Fang (International Journal of Hyperthermia, 2023)
AbstractAim The use of magnetic carbon nanotubes for multi-modal cancer treatment, incorporating both hyperthermia and drug delivery functions, has drawn substantial interest. Yet, the present method of regulating hyperthermia temperature involves manually adjusting the magnetic field intensity, adding to the complexity and difficulty of clinical applications. This study seeks to design novel magnetic carbon nanotubes capable of self-temperature regulation, and investigate their drug loading and release characteristics.Methods Using the co-precipitation method, we synthesized magnetic carbon nanotubes with a Curie temperature of 43 °C. A comprehensive investigation was conducted to analyze their morphology, crystal structure, and magnetic characteristics. To enhance their functionality, chitosan and sodium alginate modifications were introduced, enabling the loading of the antitumor drug doxorubicin hydrochloride (DOX) into these magnetic carbon nanotubes. Subsequently, the loading and release properties of DOX were investigated within the modified magnetic nanotubes.Results Under alternating magnetic field, magnetic carbon nanotubes exhibit self-regulating properties by undergoing a magnetic phase transition, maintaining temperatures around 43 °C as required for hyperthermia. On the other hand, during magnetic induction heating, the release percentage of DOX reached 23.5% within 2 h and 71.7% within 70 h at tumor pH conditions, indicating their potential for sustained drug release.Conclusions The prepared magnetic carbon nanotubes can effectively regulate the temperature during hyperthermia treatment while ensuring controlled drug release, which presents a promising method for preparing nanomaterials that synergistically enhance magnetic hyperthermia and chemotherapy drugs.